SYNTAKTIKTAHLIL THEORY IN LANGUAGE (Archive of Conferences, 2021)
In world linguistics, along with the phonological, lexical and vasemantic layers of language, scientific research is carried out to determine the semantics of functional analysis and syntactic units. There are different approaches to analysis theory in syntax, which is important in linguistics. In this regard, one of the problems to be solved in linguistics is the study of the semantics of paradigmatic and syntagmatic parts of English speech, the analysis of sentences on the basis of syntactic valence and the disclosure of the semantics of syntactic units